ELM-free and inter-ELM divertor heat flux broadening induced by edge harmonics oscillation in NSTX. (26th October 2017) - Gan, K.F.; Ahn, J.-W.; Gray, T.K.; Zweben, S.J.; Fredrickson, E.D.; Scotti, F.; Maingi, R.; Park, J.-K.; Canal, G.P.; Soukhanovskii, V.A.; Mclean, A.G.; Wirth, B.D.
Abstract: A new n   =  1 dominated edge harmonic oscillation (EHO) has been found in NSTX. The new EHO, rotating toroidally in the counter-current direction and the opposite direction of the neutral beam, was observed during certain inter-ELM and ELM-free periods of H-mode operation. This EHO is associated with a significant broadening of the integral heat flux width ( λ int ) by up to 150%, and a decrease in the divertor peak heat flux by  >60%. An EHO induced filament was also observed by the gas puff imaging diagnostic. The toroidal rotating filaments could change the edge magnetic topology resulting in toroidal rotating strike point splitting and heat flux broadening. Experimental result of the counter current rotation of strike points splitting is consistent with the counter-current EHO.